Relationship between betel quid additives and established periodontitis among Bangladeshi subjects - Rahena Akhter, Nur Mohammad (Blackwell Synergy, 2008)
Aim: To determine the relationship between betel quid chewing additives and established periodontitis in Bangladeshi subjects. Material and Methods: A total of 864 subjects participated in this study. Among them, 140 pairs of sex- and age-matched case subjects and control subjects were selected. A case was defined as a person who had at least two sites with a clinical attachment level (CAL)X6mm and at least one site with probing depth (PD)X5 mm. Subjects who did not fulfill these criteria were considered as controls. Information on sociodemographic variables, psychological stress, dental health behaviour, smoking and betel quid chewing habits was obtained. Results: Multiple logistic regression analysis showed that current betel quid chewers had greater probabilities of having established periodontal disease than did nonchewers (odds ratio53.97, po0.05). Mean PD, mean CAL, mean percentage of bleeding on probing and number of missing teeth were significantly higher in chewers of betel quid with tobacco and masala than in chewers of betel quid without such additives adjusting for age, sex, smoking habit, body mass index, dental visit pattern, stress and plaque index. Higher frequency and longer duration of betel quid chewing showed a significant relation to an increase in periodontal parameters. Conclusion: The results indicate that betel quid additives might significantly enhance periodontitis in the population studied.